2020
DOI: 10.1007/s40268-020-00322-3
|View full text |Cite
|
Sign up to set email alerts
|

Nimodipine Pharmacokinetic Variability in Various Patient Populations

Abstract: Nimodipine has been shown to improve outcomes following aneurysmal subarachnoid hemorrhage. Guidelines recommend that all patients receive a fixed dose of oral nimodipine for 21 days. However, pharmacokinetic studies have suggested variability of nimodipine pharmacokinetics in subarachnoid hemorrhage and in other patient populations. The clinical relevance of such variability is unknown. Therefore, the objective of the present review is, first, to conduct a literature review and summarize nimodipine pharmacoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 70 publications
2
16
0
Order By: Relevance
“…In our best spectral model the truncation occurs relatively close to the black hole (within a 100R g ) when the source is bright in hard X-rays, and reflec-tion from the inner disk is weak, R disk ∼ 0.2, which implies that the vertical scale height of the flow is small. Our best model is consistent with the spectral-timing model proposed for NGC 4151 by Mahmoud & Done (2020), where the main reprocessing of the X-ray radiation occurs in optically thin clouds on size scales of the BLR. The presence of the inner disk estimated in our analysis does not conflict with the dominating reprocessing in the BLR, because only a small fraction of X-rays is reprocessed in the disk.…”
Section: Truncated Disksupporting
confidence: 89%
“…In our best spectral model the truncation occurs relatively close to the black hole (within a 100R g ) when the source is bright in hard X-rays, and reflec-tion from the inner disk is weak, R disk ∼ 0.2, which implies that the vertical scale height of the flow is small. Our best model is consistent with the spectral-timing model proposed for NGC 4151 by Mahmoud & Done (2020), where the main reprocessing of the X-ray radiation occurs in optically thin clouds on size scales of the BLR. The presence of the inner disk estimated in our analysis does not conflict with the dominating reprocessing in the BLR, because only a small fraction of X-rays is reprocessed in the disk.…”
Section: Truncated Disksupporting
confidence: 89%
“…In parallel, in vitro studies on neuronal and Schwann cells showed a lower cytotoxic effect after nimodipine pre-treatment under different stress conditions [ 6 , 36 ]. The use of nimodipine has been established over the last 40 years, and its good tolerability, already proven in vivo, suggests that in addition to the standard treatment of vasospasm following subarachnoid hemorrhage, the use of nimodipine in clinical practice can be further extended [ 1 , 2 , 3 ]. In this study, the effect of nimodipine on cisplatin-induced apoptosis of inner ear hair cells was investigated for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Nimodipine belongs to the group of 1,4-dihydropyridines and exerts its effects by binding to the alpha1 subunit of L-type calcium channels, thereby decreasing calcium influx via negative allosteric inhibition [ 1 , 2 ]. Although nimodipine is one of the first calcium channel antagonists to be developed, it has been the focus of medical and scientific attention again [ 1 , 3 , 4 , 5 , 6 ]. Due to its good cerebrospinal fluid penetrability [ 2 ], which distinguishes it from other calcium antagonists of its substance class, nimodipine acts in the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, not all patients respond to this drug successfully. This variability may be due to different factors such as age, sex, comorbidities, and metabolic variations due to individual genetic susceptibility which is determined, among other factors, by the presence of polymorphic genetic variants [ 17 ].…”
Section: Introductionmentioning
confidence: 99%